Eliciting the impacts of cellular noise on metabolic trade-offs by quantitative mass imaging - A. E. Vasdekis (Nature Portfolio, 2019)
How cellular noise impacts metabolic trade-offs remains unknown. Here, the authors use a quantitative single-cell mass imaging strategy to reveal that cellular noise impacts cellular biomass and triacylglycerol accumulation, as well as protein and fatty-acid recycling under starvation, differently.